2013
DOI: 10.1128/aem.00836-13
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Salmonella and Campylobacter spp. in Environmental Farm Samples and Processing Plant Carcass Rinses from Commercial Broiler Chicken Flocks

Abstract: A prospective cohort study was performed to evaluate the prevalences and loads of Salmonella and Campylobacter spp. in farm and processing plant samples collected from 55 commercial broiler chicken flocks. Environmental samples were collected from broiler houses within 48 h before slaughter, and carcass rinses were performed on birds from the same flocks at 4 different stages of processing. Salmonella was detected in farm samples of 50 (90.9%) flocks and in processing samples of 52 (94.5%) flocks. Campylobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 35 publications
(44 reference statements)
7
96
1
4
Order By: Relevance
“…Berghaus et al (2013) reported that Campylobacter loads in postchilled samples were significantly higher than Salmonella loads, and the correlations between samples collected from the same flocks were higher for Campylobacter than Salmonella. In Northern Ireland, Salmonella and Campylobacter were found in 5.1% and 84.3% of retail raw chicken, respectively (Madden, Moran, Scates, McBride, & Kelly, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Berghaus et al (2013) reported that Campylobacter loads in postchilled samples were significantly higher than Salmonella loads, and the correlations between samples collected from the same flocks were higher for Campylobacter than Salmonella. In Northern Ireland, Salmonella and Campylobacter were found in 5.1% and 84.3% of retail raw chicken, respectively (Madden, Moran, Scates, McBride, & Kelly, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Quality control plans, mandatory testing of eggs, and hazard analysis at critical control points (HACCP) are used to reduce the spread of Salmonella in the Unites States (US). Despite these efforts, persistence of Salmonella (SALM) in the farm environment continues to be a concern for dairy, livestock and poultry operations, and growers of vegetables and leafy greens (CDC 2010;Jacobsen and Bech 2012;Berghaus et al 2013). Additionally, the risk of transport of manure-derived bacteria to surface and groundwater resources is a concern worldwide (Unc and Goss 2004;Dale et al 2010;WHO 2012;USEPA 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the US state of Iowa, alone, over 15 billion eggs are produced annually (UDSA-NASS, 2014), resulting in the generation of over 5.6 million Mg of fresh layer manure (Naber and Bermudez, 1990). Along with beneficial nutrients, PM commonly contains pathogenic bacteria, including Salmonella (SALM) (Kraft et al, 1969;Rodriguez et al, 2006;Berghaus et al, 2013). Once released to the environment, pathogens can be transported to recreational, irrigation, or drinking waters and pose a risk to human health (Rogers and Haines, 2005;Craun et al, 2010;Dale et al, 2010;USEPA, 2013), or compromise the bio-security of poultry facilities (CDC, 2010;Castiglioni Tessari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%